Wonderland : Fluxus & the game - Kelter, Jürgen; Kelter, Christina; Pellini, Pietro; Zebrastraat NV, Gent; Stichting Liedts-Meesen (Gent : Zebrastraat NV Gent, 2006)
Ben ; Blume, Bernhard Johannes ; Brecht, George ; Chopin, Henri ; d'O, Honoré ; Dufrêne, François ; Filliou, Robert ; Fischer, Th. F. ; Hansen, Al ; Hendricks, Geoffrey ; Higgins, Dick ; IRWIN ; Johnson, Ray ; Jones, Joe ; Kaprow, Allan ; Knizak, Milan ; Knowles, Alison ; Kolar, Jiri ; Köpcke, Arthur ; Kubota, Shigeko ; Maciunas, George ; Nitsch, Hermann ; Ono, Yoko ; Paik, Nam June ; Patterson, Ben ; Plessi, Fabrizio ; Polke, Sigmar ; de Ridder, Willem ; Roth, Dieter ; Rühm, Gerhard ; Saito, Takako ; Shiomi, Mieko (Chieko) ; Spanier, Wolfgang ; Spoerri, Daniel ; Tot, Endre ; Valoch, Jiri ; Villeglé, Jacques ; Vostell, Wolf ; Wewerka, Stefan ; Williams, Emmett
Publication on the occasion of the exhibition 'Wonderland : Fluxus & the game'at the Zebrastraat NV in Gent, 18.11.2006-18.02.2007
boek